2015
DOI: 10.1021/acs.jafc.5b04878
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantitation of Anthocyanins in Purple-Fleshed Sweet Potatoes Cultivated in China by UPLC-PDA and UPLC-QTOF-MS/MS

Abstract: The identification and quantitation of the anthocyanins in 12 purple-fleshed sweet potato (PFSP) cultivars ('Jihei 1', 'Xuzi 3', 'Xuzi 6', 'Zhezi 4', 'Ningzi 1', 'Ningzi 2', 'Ningzi 3', 'Ning 2-2', 'Ning 6-8', 'Guangzi 1', 'Ziluolan', and 'Qinzi 1') in China were carried out using a combination of ultraperformance liquid chromatography-photodiode array (UPLC-PDA), quadrupole-time-of-flight mass spectrometry (QTOF-MS), and tandem mass spectrometry (MS/MS) analyses. Thirteen acylated anthocyanins were tentativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 38 publications
2
47
0
1
Order By: Relevance
“…In wild‐type Ayamurasaki, peo‐based (74.75 ± 0.60%) and cy‐based anthocyanins (20.68 ± 0.85%) were dominant constituents of total anthocyanins, while pg‐based anthocyanins (4.78 ± 0.48%) were minor anthocyanins. Our results showed that the ratio of peo‐based:cy‐based:pg‐based anthocyanins was 16.36:4.53:1 in wild‐type Ayamurasaki, which was similar to other reported PSP cultivars . However, the ratios were changed significantly in Lc ‐transgenic PSP.…”
Section: Results and Disscussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In wild‐type Ayamurasaki, peo‐based (74.75 ± 0.60%) and cy‐based anthocyanins (20.68 ± 0.85%) were dominant constituents of total anthocyanins, while pg‐based anthocyanins (4.78 ± 0.48%) were minor anthocyanins. Our results showed that the ratio of peo‐based:cy‐based:pg‐based anthocyanins was 16.36:4.53:1 in wild‐type Ayamurasaki, which was similar to other reported PSP cultivars . However, the ratios were changed significantly in Lc ‐transgenic PSP.…”
Section: Results and Disscussionsupporting
confidence: 88%
“…Our results showed that the ratio of peo-based:cy-based:pg-based anthocyanins was 16.36:4.53:1 in wild-type Ayamurasaki, which was similar to other reported PSP cultivars. 21,29 However, the ratios were changed significantly in Lc-transgenic PSP. In Lc-transgenic lines, peo-based anthocyanins consisted of 38.52 ± 1.04% (Lc1), 39.36 ± 1.41% (Lc2) and 40.63 ± 1.69% (Lc3) in total anthocyanins, respectively; cy-based anthocyanins were also rich in Lc-transgenic lines, the relative contents were respectively 39.84 ± 2.72% in Lc1, 41.47 ± 1.04% in Lc2 and 42.47 ± 1.21% in Lc3.…”
Section: Results and Disscussionmentioning
confidence: 92%
“…Anthocyanins as water-soluble natural pigments are a class of flavonoids that commonly produce bright colours distributed in roots, fruits, leaves and flowers (He et al, 2016). The basic structure of the anthocyanins consists of anthocyanidins.…”
Section: Introductionmentioning
confidence: 99%
“…The basic structure of the anthocyanins consists of anthocyanidins. When the aglycon attached to sugars, they are named anthocyanins (He et al, 2016). In nature, thousands of anthocyanins have been identified, whose structures varied with the number and type of sugars, aliphatic acids and phenolic acids (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, purple-fleshed sweet potato is transformed into puree (cooked puree, dried, and powdered) and used as a functional ingredient in the food processing industries [66][67][68][69]. Purple-fleshed sweet potatoes are used to produce coloured food products with excellent colour potency [69,70]. Meanwhile, crude purple-fleshed sweet potato anthocyanins are reported to inhibit the development of Bacteroides, Prevotella and Clostridium histolyticum [71].…”
Section: Functions Of Anthocyaninsmentioning
confidence: 99%